2022
DOI: 10.3390/ijms231810666
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Forget the Bones: Incidence and Risk Factors of Metabolic Bone Disease in a Cohort of Preterm Infants

Abstract: Metabolic bone disease of prematurity (MBD) is a condition of reduced bone mineral content (BMC) compared to that expected for gestational age (GA). Preterm birth interrupts the physiological process of calcium (Ca) and phosphorus (P) deposition that occurs mostly in the third trimester of pregnancy, leading to an inadequate bone mineralization during intrauterine life (IUL). After birth, an insufficient intake of Ca and P carries on this alteration, resulting in overt disease. If MBD is often a self-limited c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
(62 reference statements)
2
10
0
Order By: Relevance
“…To diagnose MBD in accordance with the radiological alterations described by Koo's score [13], we use X-ray imaging interpreted by a single radiologist (to minimize the possibility of bias). The prevalence of MBD in our present study was 21%, showing similarity with previous reports [1,6,7,12].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To diagnose MBD in accordance with the radiological alterations described by Koo's score [13], we use X-ray imaging interpreted by a single radiologist (to minimize the possibility of bias). The prevalence of MBD in our present study was 21%, showing similarity with previous reports [1,6,7,12].…”
Section: Discussionsupporting
confidence: 92%
“…MBD is a multifactorial disease characterized primarily by inadequate bone matrix mineralization and biochemical alterations in the metabolism of phosphorus and calcium [6,7]. The data in this report indicate that VLBW infants diagnosed with MBD are at an increased risk of neurodevelopmental delay at 2 years of corrected age.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These ultra‐preterm infants are at the highest risk for metabolic bone disease of prematurity, as the fetal accumulation of minerals occurs mainly in the third trimester of pregnancy. ( 26 ) Furthermore, despite improvements in modern neonatal intensive care, these infants are still at high risk of severe neonatal morbidity, including necrotizing enterocolitis, long‐term parenteral nutrition and poor nutrition, and extrauterine growth delay. A similar tendency was also shown in previous studies as increased rates of fractures during infancy in extremely preterm newborns.…”
Section: Discussionmentioning
confidence: 99%
“…intravenous feeding of multivitamins in preterm children with lower GAs, as well as the increased oral VD consumption in infants with an increase in alkaline phosphatase concentration 2 weeks after delivery. [21][22][23] Furthermore, the univariate analysis indicated a strong correlation between VDI and PIH (P<0.05). However, the multivariable analysis revealed that the association between the two variables was not statistically significant (P>0.05), potentially attributable to the presence of multiple confounding factors.…”
mentioning
confidence: 89%